The Concrete Notion of the Ready-To-Hand Equipment: A Dialectical View on the Existential Analytic - Ravilevich Karimov, Artur (2021)
The article explores one of the aspects of Heidegger's existential analytic – everyday dealings with ready-to-hand equipment (tools). The author’s aim is to analyze the phenomenon of equipment in a broader perspective to widen the borders of everyday being-in-the-world characterized by routine nonthematic dealings with things that distract man from his true being. The author claims that in everyday use man discovers only functionality of equipment which cannot be considered its genuine grasp. The actual knowledge of things is accessible mainly to their creators for whom they are not ready-to-hand tools but the aim of their thematic investigative thought. The concrete notion of a thing is developed by those who know the origin and formation of things. Accordingly, Dasein’s everyday concern for the world is not the primary mode of being-in-the-world. The primary one is the master's non-daily creative work in his being-in-the-world which allows him/her to discover true being of things.